2006
DOI: 10.1097/01.ico.0000164831.87593.08
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Incidence and Factors Predictive of Corneal Scarring in the Collaborative Longitudinal Evaluation of Keratoconus (CLEK) Study

Abstract: Multivariate analyses of 5-year prospective data from the CLEK Study cohort showed that baseline corneal curvature, contact lens wear, corneal staining, and younger age were predictive of the development of corneal scarring. The 5-year incidence of scarring is 13.7% for the overall sample and 38.0% for those eyes with corneal curvature greater than 52 D that wore contact lenses. Contact lens wear increased the risk of incident scarring more than 2-fold. These findings suggest a causal contribution of contact l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(57 citation statements)
references
References 13 publications
(9 reference statements)
2
53
0
2
Order By: Relevance
“…However, in most patients KTCN is an isolated ocular disorder and not a feature of a specific syndrome. Clinical studies have suggested that KTCN is associated with contact lens wear, chronic eye rubbing, and atopy of the eye 1,9,10. Despite extensive study, the pathophysiological processes and the genetic etiology underlying KTCN have yet to be elucidated.…”
mentioning
confidence: 99%
“…However, in most patients KTCN is an isolated ocular disorder and not a feature of a specific syndrome. Clinical studies have suggested that KTCN is associated with contact lens wear, chronic eye rubbing, and atopy of the eye 1,9,10. Despite extensive study, the pathophysiological processes and the genetic etiology underlying KTCN have yet to be elucidated.…”
mentioning
confidence: 99%
“…Keratoconus is a multifactorial disease involving complex interaction of both genetic and environmental factors (15, 16, 1824, 48). The majority of studies narrowly focus on the identification of a single gene as the possible cause of KC; however, a large number of these studies have not been confirmed and the association of the disease with a single gene has not been established (17, 31, 48).…”
Section: Discussionmentioning
confidence: 99%
“…This examination included refraction biomicroscopic cornea and anterior segment evaluation, fundus examination, and intraocular pressure measurement. The keratoconus diagnosis was made with the classic corneal biomicroscopic findings and the use of the Collaborative Longitudinal Evaluation of Keratoconus (CLEK) Study criteria to evaluate the topographical findings [1, 9, 10]. Eyes with no other problems during the examination were included in the study.…”
Section: Methodsmentioning
confidence: 99%